2021
DOI: 10.21037/atm-21-4199
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma zedoaria petroleum ether extract reverses the resistance of triple-negative breast cancer to docetaxel via pregnane X receptor

Abstract: Background: Triple-negative breast cancer (TNBC) is characterized by its aggressiveness and poor prognosis. Docetaxel is the common chemotherapeutic drug used in the treatment of TNBC. However, resistance to docetaxel has limited the effectiveness of TNBC treatment. Petroleum ether extracts of Curcuma zedoaria (PECZ) can inhibit the proliferation of MDA-MB-231 cells. However, the effect of PECZ on docetaxel resistance is not clear. Methods: A docetaxel-resistant MDA-MB-231 (MDA-MB-231/docetaxel) cell line was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Alexanian et al [ 34 ] reported the lower expressions of CYP4A11 and CYP4A22 in normal breast tissues than those in TNBC tissues. Overexpression of CYP3A4 can promote the metabolism of docetaxel in triple negative breast cancer stem cells and further induce reduced accumulation of chemotherapy drugs in cancer cells, leading to cell drug resistance[ 22 ]. Two major metabolic enzymes of paclitaxel (CYP2C8, CYP3A4) and other genes involved in taxane heterogenic metabolism ( e.g.…”
Section: Pxr and Metabolizing Enzymes In Phase I Of Drug Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…Alexanian et al [ 34 ] reported the lower expressions of CYP4A11 and CYP4A22 in normal breast tissues than those in TNBC tissues. Overexpression of CYP3A4 can promote the metabolism of docetaxel in triple negative breast cancer stem cells and further induce reduced accumulation of chemotherapy drugs in cancer cells, leading to cell drug resistance[ 22 ]. Two major metabolic enzymes of paclitaxel (CYP2C8, CYP3A4) and other genes involved in taxane heterogenic metabolism ( e.g.…”
Section: Pxr and Metabolizing Enzymes In Phase I Of Drug Metabolismmentioning
confidence: 99%
“…, CYP1B1) are associated with drug resistance in TNBC[ 35 ]. Numerous experiments have shown that CYP enzymes are significantly upregulated in TNBC patients [ 22 , 29 , 35 ]. Therefore, the association between CYP enzymes and tumor resistance in TNBC has attracted increasing attention.…”
Section: Pxr and Metabolizing Enzymes In Phase I Of Drug Metabolismmentioning
confidence: 99%
See 3 more Smart Citations